'Juggling amidst complexity' – Hospice staff's experience of providing palliative care for infants referred from a neonatal unit. Issue 4 (August 2019) - Price, Jayne E.; Mendizabal-Espinosa, Rosa Maria
Abstract: Hospice has been pivotal to children's palliative care provision in the United Kingdom (UK) for more than 3 decades. Some hospices have recently expanded to include care of infants transferred from neonatal units as well as antenatal referrals. Despite developments evidence suggests hospice care is often not offered to parents in neonatal units (NNU). This study examines perspectives of 17 staff from 3 children's hospices regarding the challenges and opportunities caring for infants in hospice. Data was collected from 3 focus groups and analysed using a thematic approach. Findings suggest that hospice staff juggle many complex issues when caring for infants at the end-of-life. Such issues centre round the referral process from hospital services borne from an apparent reluctance of hospital staff to let go, through involving hospice. Education, partnership working, planning for all possible outcomes seems crucial in further developing quality palliative care for infants and their families.